ANALYSIS OF THE EFFECT OF FINANCIAL PERFORMANCE ON FOOD AND BEVERAGES STOCK RETURN IN INDONESIA STOCK EXCHANGE PERIOD 2015 -2019 - Muhammad Tezar (Dinasti International Journal of Education Management And Social Science, 2020)
This study aims to determine the Effect of Financial Performance on Food and Beverages Company Stock Returns on the Indonesia Stock Exchange in the 2015-2019 Period. The research method used is an associative method that aims to determine the effect or also the relationship between two or more variables. Samples were taken by techniquepurposive samplingas many as 12 companies from a population of 15 food and beverage companies on the Indonesia Stock Exchange, while the research data collection instrument for each variable is to use the ratio of financial performance and stock returns. The results of the research analysis found that the model used is the Fixed Effect Model with the results: (1) There is no significant effect between the ratio of liquidity to stock returns; (2) There is no significant effect between the ratio of activity to stock returns; (3) There is no significant effect between leverage ratio on stock returns; (4) There is a significant influence between the ratio of profitability to stock returns; (5) There is a significant influence between market value on stock returns